2013
DOI: 10.1007/s00038-013-0482-1
|View full text |Cite
|
Sign up to set email alerts
|

Linking ecosystem services and human health: the Eco-Health Relationship Browser

Abstract: Results from the systematic review were used to populate the Browser, which organizes the diverse literature and allows users to visualize the numerous connections between ecosystem services and human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 45 publications
0
51
0
1
Order By: Relevance
“…Many studies have shown that there is an intermediate link between the existence of ecosystems and public health through buffering ecosystem services (ESs), which refers to the ability of ecosystems to 'buffer' health effects (Bratman et al 2012, Jackson et al 2013, Guerry et al 2015, de Jesus Crespo and Fulford 2018. The processes of buffering ESs that are most relevant to public health can be broadly classified into the following categories: clean air and water; noise reduction; flood mitigation; heat effect reduction; climate stability; biodiversity conservation, etc Therefore, green space can modify health outcomes to a certain extent and reduce the risk of clinical diseases such as gastrointestinal diseases, respiratory diseases, and cardiovascular diseases, through the causal pathway of buffering ESs.…”
Section: Pathway 3: Linking Green Space To Ecosystem Healthmentioning
confidence: 99%
“…Many studies have shown that there is an intermediate link between the existence of ecosystems and public health through buffering ecosystem services (ESs), which refers to the ability of ecosystems to 'buffer' health effects (Bratman et al 2012, Jackson et al 2013, Guerry et al 2015, de Jesus Crespo and Fulford 2018. The processes of buffering ESs that are most relevant to public health can be broadly classified into the following categories: clean air and water; noise reduction; flood mitigation; heat effect reduction; climate stability; biodiversity conservation, etc Therefore, green space can modify health outcomes to a certain extent and reduce the risk of clinical diseases such as gastrointestinal diseases, respiratory diseases, and cardiovascular diseases, through the causal pathway of buffering ESs.…”
Section: Pathway 3: Linking Green Space To Ecosystem Healthmentioning
confidence: 99%
“…These objectives are to prioritize vulnerable populations and enhance the pedestrian environment. Greenery is a venue and stimulus for healthful behaviors including physical activity, social interaction, and engagement with nature [22]. In urban and natural areas, this quality is a key aspect of cultural, recreational, and aesthetic ecosystem services [1].…”
Section: Methodsmentioning
confidence: 99%
“…The Eco-Health Relationship Browser is an interactive graphical viewer for exploring published linkages between ES and numerous public health issues (Jackson et al, 2013). Tools such as Watershed Navigator and Raindrop are embedded within the interactive map and are designed for use with EnviroAtlas data.…”
Section: Analysis Tools and Downloadable Toolkitsmentioning
confidence: 99%